2019
DOI: 10.1039/c9ta05118j
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing percolation and ion transport in hybrid solid electrolytes for Li–metal batteries

Abstract: Hybrid solid state electrolyte structure was imaged using synchrotron nanotomography. Accessible surface area of ceramic particles in the electrolytes governs ion transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 41 publications
2
78
1
Order By: Relevance
“…Notably, there are signicant variations in both the resulting polarization overpotential and susceptibility to fracture, highlighting the need for an optimally designed hybrid structure for ideal material and transport properties. A multitude of other research with conductive oxides as llers have also been conducted with garnets, 25,28,30,81,[129][130][131] NASICONs, 31,[132][133][134][135] LISI-CONs, 136 and perovskites. 34,[137][138][139] In comparison to the oxide-polymer hybrid electrolytes, there is only a limited amount of work on sulde-polymer composites available.…”
Section: Conductive Inorganic Component: Importance Of the 3d Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, there are signicant variations in both the resulting polarization overpotential and susceptibility to fracture, highlighting the need for an optimally designed hybrid structure for ideal material and transport properties. A multitude of other research with conductive oxides as llers have also been conducted with garnets, 25,28,30,81,[129][130][131] NASICONs, 31,[132][133][134][135] LISI-CONs, 136 and perovskites. 34,[137][138][139] In comparison to the oxide-polymer hybrid electrolytes, there is only a limited amount of work on sulde-polymer composites available.…”
Section: Conductive Inorganic Component: Importance Of the 3d Networkmentioning
confidence: 99%
“…Micro-and nano-X-ray computed tomography (CT) are non-invasive techniques that can characterize morphological and structural properties. 4,182 Imaging with X-rays at high energies (keV) and low exposure times causes less polymer degradation and enables larger eld-of-views ($100 mm for Nano CT and several mm for Micro CT). 183 Micro-CT techniques can achieve sub-micron resolutions while nano-CT techniques can achieve resolutions <50 nm.…”
Section: Visualization Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the dispersion of ceramic nanoparticles or nanofibers, such as SiO 2 , Al 2 O 3 , Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 (LLZTO), or Li 1.5 Al 0.5 Ge 1.5 (PO4) 3 (LAGP), into the polymer matrices can increase the ionic conductivities, broaden the electrochemical windows, and improve the mechanical strengths of PEO-based solid polymer electrolytes (SPEs) [ 24 , 25 , 26 , 27 , 28 ]. In addition, it has also been shown that the interaction between PEO and fillers are dependent not only on different filler materials but also the morphology and size of fillers.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16–19 ] The combination of oxide‐based SEs and polymers have paved new ways to create better electrolytes which incorporate both the high ionic conductivity of the oxide‐based SE and the stable mechanical properties of polymers. [ 20–25 ]…”
Section: Introductionmentioning
confidence: 99%